Sull’origine dei demania meridionali: un’ipotesi - Vito Loré (Mélanges de la Casa de Velázquez, 2021)
In 12th-13th centuries southern Italy, there were some pieces of lands without any stable ownership and intended for cereals and livestock: the demania. They were also characterized by communitarian management. The aim of this article is to propose some hypotheses on their origins, by linking them to the aristocratic patrimonies and to the public estates during Early Middle Ages, on the basis of some exceptional sources from the Salernitan archives.